Rapid Screen for Antiviral T‐Cell Immunity with Nanowire Electrochemical Biosensors. Issue 29 (25th March 2022) - Nami, Mohsen; Han, Patrick; Hanlon, Douglas; Tatsuno, Kazuki; Wei, Brian; Sobolev, Olga; Pitruzzello, Mary; Vassall, Aaron; Yosinski, Shari; Edelson, Richard; Reed, Mark
Abstract: The ability to rapidly assess and monitor patient immune responses is critical for clinical diagnostics, vaccine design, and fundamental investigations into the presence or generation of protective immunity against infectious diseases. Recently, findings on the limits of antibody‐based protection provided by B‐cells have highlighted the importance of engaging pathogen‐specific T‐cells for long‐lasting and broad protection against viruses and their emergent variants such as in SARS‐CoV‐2. However, low‐cost and point‐of‐care tools for detecting engagement of T‐cell immunity in patients are conspicuously lacking in ongoing efforts to assess and control population‐wide disease risk. Currently available tools for human T‐cell analysis are time and resource‐intensive. Using multichannel silicon‐nanowire field‐effect transistors compatible with complementary metal−oxide−semiconductor, a device designed for rapid and label‐free detection of human T‐cell immune responses is developed. The generalizability of this approach is demonstrated by measuring T‐cell responses against melanoma antigen MART1, common and seasonal viruses CMV, EBV, flu, as well as emergent pandemic coronavirus, SARS‐CoV‐2. Further, this device provides a modular and translational platform for optimizing vaccine formulations and combinations, offering quick and quantitative readouts for acquisition and persistence of T‐cell immunity against variant‐driven pathogens such as flu and pandemic SARS‐CoV‐2. Abstract : Using complementary metal−oxide−semiconductor (CMOS)‐compatible multichannel silicon‐nanowire field‐effect transistors, a device for rapid and label‐free detection of human T‐cell immune responses is developed. The generalizability of this approach is demonstrated by measuring T‐cell responses against melanoma antigen MART1, common viruses CMV, EBV, flu, as well as emergent SARS‐CoV‐2. Nanowire devices successfully assess SARS‐CoV‐2‐specific T‐cells directly from peripheral blood samples of donors, demonstrating potential point‐of‐care applications in rapid detection of antigen‐specific T cells.